Anticipating Arrears to the IMF Early Warning Systems - Oka, Chikako (IMF Working Papers; Working Paper, 2003)
This paper attempts to predict the incidence of arrears to the International Monetary Fund (IMF) by modifying and applying two of the major early warning systems for currency crises: the "signals" approach proposed by Kaminsky, Lizondo, and Reinhart (1997) and the probit-based alternative developed by Berg and Pattillo (1998). The results, based on both in-sample and out-of-sample tests, appear encouraging. While the unique nature of IMF arrears poses some challenges, the models could be useful tools for identifying countries at high risk of incurring arrears to the IMF.